Collapse of the global order on drugs : from UNGASS 2016 to Review 2019 - Klein, Axel; Stothard, Blaine (Emerald Publishing Limited, 2018)
This book describes the events, activities and negotiations leading up to the 2016 UN General Assembly Special Session on international drug policy. A range of respected authors from International institutions, academia and civil society organisations detail the background to the negotiations and the outcome; and possible future scenarios for continued reform and change at the High Level Review in 2019. The chapters include consideration of the positions taken by blocs and nation-states at all points on the prohibition reform continuum. Topics covered include discussions on the importance of human rights, access to essential medicines and the role played by cannabis in revealing the contradictions and divisions in both national and international contexts. The break-down of the previous international consensus on 'the world drug problem' is clearly described and analysed, as is the slow progress being made to the adoption of a human rights and health-based approach to currently illegal drugs. Consideration is also given to the nations and arguments which continue to defend prohibition and its repressive impacts on national populations, and the prioritising of geo-politics over population health this represents in practice. There are lessons and examples here for international politics and national policy reform.